SOCIAL CORRELATES OF FEMALE INFERTILITY IN UZBEKISTAN - JUMAYEV, IZATULLA (Nagoya J Med Sci, 2012)
The purpose of this matched case-control study was to investigate the social correlates of primary infertility among females aged 35 years or less. The study was conducted in the Clinics of Samarkand Medical Institute, Uzbekistan, among 120 infertile and 120 healthy women matched by age, residential area, and occupation from January to June 2009. Data were collected by face-to-face interviews using a structured questionnaire. Median duration of infertility was 10.0 months (interquartile range = 6.0–13.0). The rate of remarriage was 3.5 times higher among infertile women compared with healthy subjects. Insufficient family income, poor quality of life, life stress, and discontentment with daily routines as well as ‘bad’ relationships with family members (husband, mother- and father-in-law) were significant correlates of female infertility. Infertile women were more likely to underestimate the importance of sexual intimacy, and a negative attitude to sex. Female infertility is associated with various social correlates leading to higher remarriage rates and to further complicating the problem of infertility. Thus, a correction of women’s basic attitudes and their relationships to their surrounding social habitat should be an essential component of any program of infertility management.